Comparison of Botu-bov and Tris as Freezing Extenders of Buffalo Sperm Recovered from Epididymal Cauda - Camargos, Aline Sousa [UNESP]; Oba, Eunice [UNESP]; Monteiro, Gabriel Augusto [UNESP]; Fabres, Yame [UNESP]; Sancler-Silva, Robaina [UNESP]; Zorzetto, Mariana [UNESP]; Dias Maziero, Rosiara Rosaria [UNESP]; Papa, Frederico Ozanam [UNESP]; Ramos, Alcides Amorim [UNESP] (Int Buffalo Information Ctr, 2013)
Valuable genetic material can be preserved by the cryopreservation of epididymal sperm. This study evaluated the viability of pre-freezing and post-thawed sperm samples recovered from the epididymal cauda of buffaloes. Epididymides from eight Murrah buffaloes with 18 months of age were used. Semen samples were diluted in two different freezing extenders: Botu-bov (BB) and Tris (TRIS). Immediately after slaughter, both testicles from each animal were collected and transported at 4 degrees C for six hours interval. In laboratory, the removed epididymides were flushed to obtain sperm and the fractions were diluted in both freezing extenders (BB and TRIS). Semen doses were analyzed before and after frozen at -196 degrees C. BB and TRIS pre-freezing results were 38.54 +/- 22.33%(b) and 14.17 +/- 12.78%(a) for total motility (TM), 25.00 +/- 16.12(a) and 9.44 +/- 9.11(a) for progressive motility (PM), 7.21 +/- 0.98(a) and 5.09 +/- 2.65(a) for percentage of rapid cells (RAP), 91.08 +/- 12.53(b) and 63.33 +/- 31.47(a) for velocity of trajectory (VAP), 73.54 +/- 20.17(b) and 49.50 +/- 9.11(a) for linear progressive velocity (VSL), 172.21 +/- 24.55(a) and 116.94 +/- 59.48(a) for curvilinear velocity (VCL), respectively (P < 0.05). BB and TRIS post-thawing results were 42.25 +/- 21.50(b) and 17.62 +/- 19.46(a) for TM, 27.25 +/- 24.86(a) and 18.00 +/- 13.68(a) for PM, 7.35 +/- 0.98(a) and 6.26 +/- 1.13(a) for RAP, 91.42 +/- 16.86(a) and 75.96 +/- 13.17(a) for VAP, 67.96 +/- 12.13(a) and 60.04 +/- 10.42(a) for VSL, 177.54 +/- 23.53(b) and 141.29 +/- 24.97a for VCL, respectively (P < 0.05). The sperm recovered from the epididymal cauda, after 6 h storage of epididymides at 5 degrees C ensures sperm preservation demonstrating that the diluent Botu-bov had higher total motility both pre-and post-freezing when compared with TRIS. Additionally, the sperm frozen with the diluent Botu-bov showed higher values of VSL at post-thawing. These findings may reflect in improvement of conception rates.
Keywords: semen; Bubalus bubalis; epididymal; freezing